Effect of intelligent speed adaptation technology on older drivers' driving performance. Issue 3 (1st April 2015) - Guo, Weihong; Blythe, Philip T.; Edwards, Simon; Pavkova, Katerina; Brennan, Dan
Abstract : Excess speeding on roads with a low‐speed limit is a key error in drivers of all ages although the reasons for speeding can be significantly different. Drivers aged over 60 are generally more cautious, and take fewer risks than younger aged drivers. This study investigates whether Intelligent Speed Adaptation (ISA) technology can assist older drivers in maintaining vehicle speed. The technology can be employed in three ways: advisory (AISA), differential (DISA) and mandatory (MISA). Twenty‐six drivers aged over 60 years old participated along with a comparison group of 16 experienced younger drivers aged under 60. All drivers completed four driving tasks in a driving simulator with and without ISA. Results show improvements in speed and lane‐keeping performance vary depending on the type of ISA and driver age and training in effective use of ISA is needed for drivers of all ages. The study is one component of a wider research programme exploring how ITS could potentially help older people overcome some of the difficulties they experience with driving as they age and hopefully help them remain safe drivers for longer, a benefit both to the individual and society.